Role of Pro- and Anti-Inflammatory Cytokines in Rheumatoid Arthritis: Correlation with Disease Activity. - Al-Hassan, Ahmed A. H. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Rheumatoid arthritis (RA) is a chronic and debilitating autoimmune disease characterized by chronic inflammation with subsequent cartilage and bone destruction. Cytokines are  key mediators of inflammation and can be found in abundance both in the joint and blood of patients. This study was designed to evaluate the role of pro- and anti-inflammatory cytokines in pathogenesis of RA, as well as study the correlation among these cytokines.Patients and methods: Forty patients with RA and thirty age-matched healthy controls were included in this study. Serum cytokines were measured by enzyme-linked immunosorbent assay.Results: The serum levels of pro-inflammatory cytokines (IL-1α, IL-2, IL-6, IL-8, IL-12 and TNF-α) were significantly higher in RA patients than in healthy controls (p